Perspektif Hukum Islam Dalam Pendidikan Jasmani - Seri Mughni Sulubara; Amrizal Amrizal (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
For a Muslim, the body is a means of worshiping the Khaliq (Allah SWT), both worship that is hablu minan-nas and hablu mina-Allah. Al-Ghazali views the physical aspect as a means to achieve human goals, and a means to carry out religious obligations. The aim of this research is to find out the Islamic perspective on physical education. The research method used is library research. Therefore, this research was obtained from reading results sourced from articles, books, and websites that contain material relevant to this research. The findings in this study are that Islamic law regulates physical education with the aim of being able to get used to healthy living and discipline in maintaining cleanliness, eating patterns, dress patterns, activity patterns and resting as an effective method of maintaining physical health.